Preparation of Al2O3-ZrO2 scaffolds with controllable multi-level pores via digital light processing. Issue 15 (December 2020) - Jiao, Chen; Gu, Jiajun; Cao, Ying; Xie, Deqiao; Liang, Huixin; Chen, Ruoyu; Shi, Tianshu; Shen, Lida; Wang, Changjiang; Tian, Zongjun; Yi, Xinyu
Abstract: Multi-level porous material based on additive manufacturing, is a potentially disruptive material across multiple industries, including medical implants, thermal insulation and filtration. In this study, we propose a novel approach to fabricate materials with controllable pores via digital light processing (DLP) and decomposition of Al(OH)3 . DLP can be used to fabricate macro pores bigger than 300 μm. And the decomposition of Al(OH)3 can result in micro pores of about 1 μm inside the scaffolds. The process parameters of curing, debinding and sintering temperature (1100−1500 ℃) of ceramic scaffolds with containing proportion of Al(OH)3 (0−60 wt.%) were examined. The results indicated multi-level porous ceramic scaffold has controllable porosity and pore size distribution and meets the requirement of implant strength. Biological test show that ceramic scaffolds with multi-level pores promoted osteoblast proliferation and adhesion. The multi-level porous ceramic scaffolds prepared by DLP and decomposition of Al(OH)3 have great prospects for the application in bone implants.